Postprandial response improvement via safety layer in closed-loop blood glucose controllers. (February 2015) - León-Vargas, Fabian; Garelli, Fabricio; De Battista, Hernán; Vehí, Josep
Abstract : Highlights: The paper presents and intensively evaluates a method for reducing the incidence of postprandial hypoglycemia in patients with type 1 diabetes. The method adapts the glucose set-point when the insulin-on-board estimation reaches a given clinical constraint. Through a very challenging test scenario it is shown that the method not only reduces the hypoglycemia events but also allows reducing the postprandial glucose excursion. Abstract: Traditional type 1 diabetes therapies are prone to show poor glucose regulation especially in the postprandial period owing to both physiological and technological limitations. Although a closed-loop controller for glucose regulation has to be tuned to minimize the postprandial excursion and avoid late hypoglycemia, the intrinsic limitations of the problem lead to a trade-off between postprandial peak and late hypoglycemia risk. This paper reveals through an intensive in-silico study with multiple controller tuning combinations that a novel safety layer for glucose controllers, the so-called SAFE loop (Revert et al., 2013), not only reduces the hypoglycemia events but also allows reducing the postprandial glucose excursion, thus breaking the implicit trade-off present in single controllers. The SAFE outer loop monitors the estimated amount of insulin on board, and modifies the control action if it is close to a unique constraint which can be adjusted with clinical criteria. A very challenging test scenario is here implemented including the rate of blood glucose appearance from intakes of mixed meals, diurnal and day-to-day time-varying metabolic changes, inherent drawbacks in sensor and actuator, and other realistic conditions. The results show a significant reduction of hypoglycemia events when SAFE is added, regardless the closed-loop glucose controller, together with a potential postprandial response improvement.